Flexible Ru/Graphene Aerogel with Switchable Surface Chemistry: Highly Efficient Catalyst for Room‐Temperature CO Oxidation. Issue 10 (24th February 2016) - Li, Wencheng; Zhang, Huanhuan; Wang, Jitong; Qiao, Wenming; Ling, Licheng; Long, Donghui
Abstract : Self‐assembly and functionalization of macroscopic graphene architectures are generally required to offset the drawbacks of pure graphene sheets for practical applications. Herein, a macroscopic 3D flexible well‐faceted Ru nanocrystalline‐decorated graphene aerogel is prepared by a unique polyol‐mediated solvothermal method. The key to the synthesis is relied on ethylene glycol as the solvent and reducing agent, which can simultaneously reduce graphene oxide (GO) and Ru 3+ ions and further self‐assemble into the 3D aerogel network. The resultant Ru/graphene aerogels possess a low density of 17.3 mg cm −3, highly porous structures, good flexible ability, and excellent electrical conductivity (333 S m −1 ). The catalytic properties of these Ru/graphene aerogels for CO oxidation, especially addressing the pretreatment effects on the catalytic activity and the role of surface oxygen species, are investigated. It has been shown that mild air pretreatment can switch the surface chemistry of nanocrystalline Ru, inducing the formation of highly active oxygen‐vacancy RuO x . These pretreated aerogels thus can deliver 100% CO conversion with long durability at room temperature, and can work effectively at ultrahigh space velocity. These unique characteristics of Ru/graphene aerogels point to their promising application in in‐door air quality control. Abstract : Functionalization of 3D graphene aerogels is generally required to offset the drawbacks of pure graphene in the specific desired functionality. Here an easy self‐assembly approach is developed to prepare a 3D flexible Ru nanoparticle/graphene aerogel by means of a polyol‐mediated solvothermal method. The resultant Ru/graphene aerogels possess a low density, good flexible ability, and extraordinary catalytic activity toward room‐temperature CO oxidation.